Causal impact of malnutrition on mortality among adults hospitalized for medical illness in sub-Saharan Africa: what is the role of severe sepsis? - Asiimwe, Stephen B.; Amir, Abdallah; Vittinghoff, Eric; Muzoora, Conrad (BMC Nutrition, 2015)
Background: In sub-Saharan Africa, malnutrition is associated with mortality in adults hospitalized for medical illness. However, it remains unclear whether this association is causal, and if causal, what the potential mediators are. We assessed whether malnutrition is causally related to mortality among hospitalized adults, and whether severe sepsis plays a mediating role. Methods: We analyzed data from a cohort study of adults hospitalized for any medical illness in Uganda. We measured malnutrition using mid-upper arm circumference (MUAC). We used a directed acyclic graph to identify a minimum sufficient adjustment set of confounders in order to estimate the overall effects of malnutrition on mortality. We then used recently developed statistical methods to determine whether mortality in malnourished patients is mediated by severe sepsis. Results: We analyzed data of 318 adults. Median age was 37 (interquartile range [IQR] 27 to 56), and 25 % (n = 80) were malnourished according to MUAC. Malnourished patients were more likely to be HIV positive (64 % versus 39 %, p < 0.001), more severely ill (median MEWS 5, IQR 3 to 7 versus 4, IQR 2 to 6, P = 0.003), and to have both any sepsis (66 % versus 39 %, p < 0.001) and severe sepsis (51 % versus 20 %, P < 0.001) compared to normally nourished patients. After adjusting for the modified early warning score at admission, tuberculosis, HIV status, education status, age, and sex, malnourished patients remained at 3.0-fold (95 % CI: 1.5, 6.1, P = 0.002) increased odds of having severe sepsis at admission, and at 2.1-fold (95 % confidence interval [CI]: 1.2, 3.7, P = 0.008) increased odds of dying by 30 days’ post-admission. Only a small proportion of the effects of malnutrition on mortality were mediated by severe sepsis; overall, malnutrition increased the risk of death by 16.8 percentage points (95 % CI: 4.1, 29.4), but only 1.1 percentage points (95 % CI: −2.1, 4.4) absolute risk difference was mediated by severe sepsis. Conclusion: Our data suggest that malnutrition increases mortality in adults hospitalized for medical illness; thus, interventions against malnutrition in this population may reduce mortality. As severe sepsis did not mediate a large proportion of the effects of malnutrition on mortality, future studies are recommended to investigate other potential mediators.
Keywords: Malnutrition; Hospitalized adults; Mortality; Severe sepsis; Causal impact; Mediation